Tumor-expressed inducible nitric oxide synthase controls induction of functional myeloid-derived suppressor cells through modulation of vascular endothelial growth factor release - Jayaraman, Padmini; Ramacher, Marcel; Umansky, Viktor (The journal of immunology, 2012)
Inducible NO synthase (iNOS) is a hallmark of chronic inflammation that is also overexpressed in melanoma and other cancers. Whereas iNOS is a known effector of myeloid-derived suppressor cell (MDSC)-mediated immunosuppression, its pivotal position at the interface of inflammation and cancer also makes it an attractive candidate regulator of MDSC recruitment. We hypothesized that tumor-expressed iNOS controls MDSC accumulation and acquisition of suppressive activity in melanoma. CD11b+GR1+ MDSC derived from mouse bone marrow cells cultured in the presence of MT-RET-1 mouse melanoma cells or conditioned supernatants expressed STAT3 and reactive oxygen species (ROS) and efficiently suppressed T cell proliferation. Inhibition of tumor-expressed iNOS with the small molecule inhibitor L-NIL blocked accumulation of STAT3/ROS-expressing MDSC, and abolished their suppressive function. Experiments with vascular endothelial growth factor (VEGF)-depleting Ab and recombinant VEGF identified a key role for VEGF in the iNOS-dependent induction of MDSC. These findings were further validated in mice bearing transplantable MT-RET-1 melanoma, in which L-NIL normalized elevated serum VEGF levels; downregulated activated STAT3 and ROS production in MDSC; and reversed tumor-mediated immunosuppression. These beneficial effects were not observed in iNOS knockout mice, suggesting L-NIL acts primarily on tumor- rather than host-expressed iNOS to regulate MDSC function. A significant decrease in tumor growth and a trend toward increased tumor-infiltrating CD8+ T cells were also observed in MT-RET transgenic mice bearing spontaneous tumors. These data suggest a critical role for tumor-expressed iNOS in the recruitment and induction of functional MDSC by modulation of tumor VEGF secretion and upregulation of STAT3 and ROS in MDSC.
Prepublished online 23 April 2012
Gesehen am 20.08.2018